Women development program a means to increase women's political and economic participation (a case study of the rural improvement club in Hamtic, Antique) - Draper, Dianne E.; Gavilla, Maileen G. (2003.)
This study looked into the impact of the Rural Improvement Club on the political and economic participation of its members. The RIC was analyzed using the Women in Development (WID) and the Gender and Development (GAD) frameworks. The study was conducted at Hamtic, Antique. There were 15 respondents chosen from the five most active members of the RIC Federation. They were chosen based on the assumption that they were more politically involved due to the fact that they were officers of the said organization. The measures that the researchers used for political participation include voting, participating in community meetings and discussions, occupying elective positions in the government, participating in elections as watchers and campaign officers, communicating and writing to government officials, and increasing knowledge about politics. Economic participation includes obtaining jobs with pay and increased contribution to the family income. The result of the study showed that the RIC only enhanced women's political participation. it greatly contributed to the economic participation of its members.
Thesis (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo
Keywords: The Rural Improvement Club -- Hamtic, Antique; Women's Political Participation; Women's Economic Participation